Environmental tracers as a tool in groundwater vulnerability assessment - Wachniew, Przemys?aw (Acque Sotterranee - Italian Journal of Groundwater, 2015)
Environmental tracers are physical properties and chemical components of water whose spatial and temporal differentiation is used to infer information on the pathways and dynamics of water and solutes movement through the environment. The quantitative and qualitative insights into the functioning of groundwater systems derived from tracer observations is useful for the physically based and operational assessments of vulnerability of groundwater quality to human pressures. This tracer-based information concerns identification of the hydraulic connections between the source areas of pollution and groundwater receptors and evaluation of the ability of the unsaturated and saturated zones to delay and attenuate spreading of pollutants. Particularly important are distributions of water transit times which can be inferred from tracer observations by use of the lumped parameter models. The transit time distributions contain information on the lag-times, attenuation and persistence of pollutants in groundwater systems and are a basis for designing various indexes of vulnerability. Despite the advantages of environmental tracers in vulnerability assessment and despite the advances in analytical techniques application of tracers in this field is limited. This work presents the understanding of groundwater vulnerability in the context of risk assessments, explains the basic concepts of the application of the environmental tracers, discusses potential applications of tracers in assessing the intrinsic groundwater vulnerability and briefly presents examples of such applications.